RESPON PADI GOGO (Oryza sativa L.) TERHADAP APLIKASI BIOCHAR SEKAM PADI DAN PUPUK KANDANG SAPI - Killa, Yonce Melyanus; Jawang, Uska Peku (Jurnal Agro Indragiri, 2024)
Upland rice is one type of local rice that is still cultivated and has the potential to be developed. However, its productivity is still low, so it is necessary to add nutrients to increase its productivity. This research was conducted with the aim of looking at the response of upland rice to the application of rice husk biochar and cow manure. The tools and materials used in this study were: polybag, inceptisol soil, rice husk biochar, cow manure, camera, upland rice seed label paper, and stationery. This study used a completely randomized design with 5 treatments and 4 replications. The treatments in this study were BP0: control (without biochar and manure), BP1: biochar 5 t ha-1 + manure 5 t ha-1; BP2: biochar 10 t ha-1 + manure 5 t ha-1, BP3: biochar 5 t ha-1 + manure 10 t ha-1, BP4: biochar 10 t ha-1 + manure 10 t ha-1. The results of this study were that the application of rice husk biochar 10 t ha-1 + manure 5 t ha-1 gave the highest effect on plant growth which included plant height, number of leaves and number of tillers of rice plants.